The long-distance leader revised rules for remarkable remote and hybrid leadership - Eikenberry, Kevin 1962-; Turmel, Wayne (Berrett-Koehler Publishers, Inc., 2024)
"Now with additional chapters and guidance on hybrid workplaces, this foundational bestseller has new rules and timeless insights for leading others at a distance. Leadership First, Location Second. As more organizations adopt a remote workforce, the challenges of leading at a distance become more urgent than ever. The cofounders of the Remote Leadership Institute, Kevin Eikenberry and Wayne Turmel, show leaders how to guide their teams by recalling the foundational principles of leadership whether their teams are scattered globally or just working from home a few days a week. To make leadership happen today we must rely more on technology and far less on face-to face communication. This can make the work of leaders and team members more isolating, frustrating, and stressful. This book is for motivated leaders who want to get a handle on their remote work and teams. The book is built around the authors' 3O model: Ourselves, Others, and Outcomes. They explain how to cultivate the mindset and attitude needed to lead oneself effectively at a distance; how to engage others when you're not physically present; and what processes and tools to use to make sure dispersed teams achieve the desired outcomes. In some ways the job of a leader has changed less than we think. Leadership is leadership and people are people. But (and it is a pretty big but) how we do it needs to evolve if we want the results and outcomes our organizations demand, leaders need, and their team members deserve"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Leadership